2015
DOI: 10.1590/1678-4499.0140
|View full text |Cite
|
Sign up to set email alerts
|

Redes neurais artificiais na predição da produtividade de milho e definição de sítios de manejo diferenciado por meio de atributos do solo

Abstract: O entendimento dos fatores que influenciam a produtividade é essencial para o sucesso produtivo e para adoção de manejo diferenciado em sítios específicos. Na busca de alternativas para predizer a produtividade de grãos de milho a partir de atributos do solo, uma alternativa consiste no uso de redes neurais artificiais (RNAs). Diante disso, o presente estudo teve por objetivo avaliar a eficácia de adoção de atributos do solo por interface da análise de regressão, e das RNAs no estabelecimento de sítios de mane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 22 publications
0
27
0
3
Order By: Relevance
“…Promising results with the use of artificial neural networks were found by Leal et al (2015) adopting soil attributes in the simulation of corn grain yield. In study on adaptability and stability of cowpea, Teodoro et al (2015) found similarity of the parameters obtained by the traditional method of Eberhart & Russel (1966) and the use of artificial neural networks.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Promising results with the use of artificial neural networks were found by Leal et al (2015) adopting soil attributes in the simulation of corn grain yield. In study on adaptability and stability of cowpea, Teodoro et al (2015) found similarity of the parameters obtained by the traditional method of Eberhart & Russel (1966) and the use of artificial neural networks.…”
Section: Resultsmentioning
confidence: 99%
“…Simulation models are essential in the identification of factors that influence agricultural production and moreefficient managements (Mello & Caimi, 2008;Leal et al, 2015). Artificial intelligence (AI) techniques have emerged as an alternative in the development of simulation and optimization models (Leal et al, 2015;Soares et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…kg ha -1 ) were selected. These variables were normalized to equalize the ANN input data (Leal, Miguel, Baio, Neves, & Leal, 2015) so that the initial weights of the variables were assumed to be equivalent at the beginning of the training, thus avoiding the difficulties posed by variables with different weights that can prevent the ANN from converging.…”
Section: Methodsmentioning
confidence: 99%
“…The data were divided into the different stages: 70% used for training and 30% for generalization (validation), and processed through software NeuroForest 3.3 (Binoti et al, 2014). The training algorithm used was Resilient Backpropagation, which, according to Leal et al (2015), it is the most skilled and recommended choice for Multilayer Perceptron ANN type.…”
Section: Training and Evaluation Of Annmentioning
confidence: 99%